Nutritional Knowledge and Cultural Food Beliefs on Dietary Practices of Pregnant Women - Raffy O. Jembi; Abimbola A. Emmanuel; Abdurazaq T. Ibraheem (International Journal of Home Economics, Hospitality and Allied Research, 2023)
The paper assessed the nutritional knowledge and cultural food beliefs on dietary practices of pregnant women in Epe Local Government Area, Lagos State, Nigeria. A descriptive research design was adopted for this study. The population of the study consisted of all registered pregnant women in seven (7) antenatal clinics in Epe Local Government Area of Lagos State. A sample size of 270 was drawn using proportionate sampling technique. The collected data were analyzed using frequency, percentage, and the Chi-square test of association. The significance level was set at p < 0.05. The results showed a statistically significant relationship between knowledge of nutrition and dietary practices, χ2 (2) = 78.201, p<0.05. However, there was no statistically significant relationship between cultural food beliefs and dietary practices, χ2 (1) = 1.151, p>0.05. The finding also showed that cultural food beliefs do not influence the dietary practices of pregnant women. The study recommends that the government and health agencies should continuously train health workers on nutritional issues, particularly on how to enhance the nutritional knowledge of expectant pregnant women prior to conception. This will help potential mothers improve their dietary practices.